A clenbuterol detection method based on magnetic separation up-conversion fluorescent probe - Xin-Jie Song; Fei Ye; Yao Zhang; Juan Sun; Xuping Shentu; Xiaoping Yu; Wei Li; Yuan-Feng Wu (Food Chemistry: X)
In this study, a fluorescence detection method combining aptamer-modified up-conversion nanoparticles (UCNPs) and magnetic nanoparticles (MNPs) was developed for detection of Clenbuterol (CLB). The aptamer-modified magnetic NPs captured CLB, which reacted with the aptamer-modified UCNPs and generated a sandwich complex. The aptamer-modified UCNPs acted as a fluorescence source. The MNP-CLB-UCNP complex was retrieved from the solution using an magnetic field, and the fluorescence intensity was detected by fluorescence spectrophotometry with excitation and emission spectra at 980 nm and in the 400–800 nm region, respectively. The results showed that the fluorescence intensity gradually increased with increasing concentrations of CLB with a good specify. The method was highly sensitive for the quantification of CLB, with a limit of detection of 0.304 ng mL−1. The recovery rate of CLB from pork samples ranged from 84 % to 94.87 %. This fluorescence method enables the sensitive, precise, and accurate quantification of CLB residues in pork samples.